2014
DOI: 10.1155/2014/950903
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated PD-1 Expression Is Associated with the Development of Systemic Lupus Erythematosus, but Not the PD-1.1 Allele of the PDCD1 Gene

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease with complicated genetic inheritance. Programmed death 1 (PD-1), a negative T cell regulator to maintain peripheral tolerance, induces negative signals to T cells during interaction with its ligands and is therefore a candidate gene in the development of SLE. In order to examine whether expression levels of PD-1 contribute to the pathogenesis of SLE, 30 patients with SLE and 30 controls were recruited and their PD-1 expression levels in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
2
18
1
Order By: Relevance
“…However, the co-IR expression patterns on various lymphocyte subsets show considerable disease-dependent variation. For example, PD-1 is increased in CD4 + and CD8 + T and NK cells from lupus patients (36,37), and in CD3 + T cells from psoriatic arthritis patients (38), while in SSc it is only significantly enhanced in Tregs and γδ T cells (Fig. 1C).…”
Section: Discussionmentioning
confidence: 95%
“…However, the co-IR expression patterns on various lymphocyte subsets show considerable disease-dependent variation. For example, PD-1 is increased in CD4 + and CD8 + T and NK cells from lupus patients (36,37), and in CD3 + T cells from psoriatic arthritis patients (38), while in SSc it is only significantly enhanced in Tregs and γδ T cells (Fig. 1C).…”
Section: Discussionmentioning
confidence: 95%
“…It is reported that PD-1/PD-L1 signaling pathway plays negative regulation roles in autoimmune diseases such as glomerular nephritis, autoimmune encephalomyelitis, psoriatic arthritis, and Sjogren's syndrome. [11][12][13][14][15] In addition, activation of PD-1/PD-L1 signaling pathway in rheumatoid arthritis patients effectively inhibits the proliferation of Th1 and Th17 cells and the secretion of IFN-g and IL-17 cytokines. 16 sPD-1 is the soluble form of PD-1 that is obtained by phosphoric acid hydrolysis of membrane type PD-1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated the frequentness of PD1.1 G/A (rs36084323) in the Chinese Han population (49%), but its' scarcity in Europeans (1%), which may be associated with the Chinese Han population more susceptibility to SLE [4]. Nonetheless, Jiao et al observed no correlation between SNP PD1.1 G/A (rs36084323) and enhanced expression of PD1 in PBMCs from SLE patients [7]. As the PD1.1 is located within PD1 promoter region and the SNP at this location could exert no function, further study is required to shed the light on the precise role of this SNP in the pathogenesis of JSLE.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the development of lupus-like syndrome has been identified in PD-1 deficient mice [4]. Several association studies have been conducted to assess the potential correlations of various single nucleotide polymorphisms (SNPs) in PDCD1 gene, known to affect the level of PD-1 expression, with adult-onset SLE proneness so far [4][5][6][7][8][9]. However, there is a paucity of data regarding the associations of PDCD1 SNPs with individuals' susceptibility to JSLE.…”
Section: Introductionmentioning
confidence: 99%